Assessment on how pre-service science teachers view the nature of science - Colagrande, Elaine A; Martorano, Simone A.A; Arroıo, Agnaldo (Journal of Turkish Science Education, 2016)
This study presents the results of a pedagogical activity developed with a group of pre-service science teachers from a Brazilian Federal University. The activity was designed so that the pre-service teachers (PSTs) could express their conceptions about the nature of science through several ways of representation by means of drawing, writing, or diagrams. The PSTs were asked to describe their thoughts about five themes: science in human life, the construction of scientific knowledge, the work of a scientist, the relationship between science and technology, and science and society. Our findings brought to light very important points about the nature of science as well as further discussions with the group. Indeed, activities such as the proposed one can lead PSTs to a meta-reflection about their conceptions about the nature of scientific knowledge by aiding them in the construction of new models and strategies for science teaching in their classroom practices.
Keywords: Nature of science; scientific knowledge; teacher training